Article 162 of the Polish Civil Procedure Code – application, functions and its role in the civil process - Marciniak, Sławomir (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2013)
The paper aims to analyse article 162 of the Polish Civil Procedure Code. Pursuant to the article mentioned, parties are not only allowed but also obliged to notify the court of all procedural errors it has made. The purpose of this legal institution is to hasten and organize civil procedure. This paper illustrates the history of subject regulation. Subsequently,it focuses on the application and role of article 162 of the Polish Civil Procedure Code in current civil procedure. After analysing those matters, the conclusion is presented that the regulation provided by article 162 is inappropriate to the correct shaping of current civil procedure. The instant removal of all procedural errors that the court makes is essential to appropriate procedure in many ways.